DARI LISAN KE DIGITAL: PEMBERDAYAAN LABORATORIUM TEKNIK MESIN MELALUI PANDUAN OPERASIONAL BERBASIS QUICK RESPONSE CODES (QR CODES) DI UNIVERSITAS HALU OLEO - Muhammad Idris Putra; Budiman Sudia; Prinob Aksar; Bahdin Ahad Badia; La Rahman; Muhammad Irwan Syahib; Citra Yurnidar Syah; Anita Yuliana (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Optimizing laboratory management is support safe and effective learning activities. In the Design and Machining Process Laboratory, Faculty of Engineering, equipment operation has largely depended on verbal instructions from laboratory staff, increasing the potential for operational errors & workplace accidents. This commu nity service program aimed to develop digital equipment operating manuals integrated QR Codes to improve users' independence in laboratory activities. A participatory approach was employed through needs assessment, equipment inventory, manual develop ent based on technical references and occupational health and safety standards, integration into QR Code-linked digital flip books, dissem ination, and evaluation. The results demonstrate that the digital manuals can be accessed instantly by scanning QR Codes attached to each piece of equipment, enabling students to obtain operational guidance independently. This innovation enhances the effectiveness of laboratory practice, minimizes equipment misuse, and promotes a stronger occupational safety culture, making it a practical and sustainable model for laboratory management in higher education